Y. S. Bondarenko. The phonemic tendencies of Estuary English - Bondarenko Y. S. (Philological Treatises, 2020)
The phonemic tendencies of Estuary English are investigated in this paper. The description of phonemic variety of this pronunciation standard is analyzed. The popularity of the Pronunciation Standard in mass media is given.